Men's Sheds: Enabling environments for Australian men living with and without long-term disabilities - Hansji, N.; Wilson, N.; Cordier, Reinie (Blackwell Publishing Ltd, 2015)
© 2014 John Wiley & Sons Ltd. The health of Australian men has recently received greater attention. Men's Sheds are named in national policy as an exemplar community-based organisation for the betterment of men's psychosocial health; yet, the evidence base to support this is limited. This study investigates the comparative experience of men with long-term disabilities and men without long-term disabilities who go to a Men's Shed and to what extent this provides these men with an enabling, as opposed to disabling, environment. Data were collected from 12 individual interviews with men with long-term disabilities (5) and men without long-term disabilities (6), including 1 interview with the male Men's Shed Coordinator (MSC); participant observation within the shed; and a document received from the female MSC regarding the funding the Shed receives. Interviews explored the men's experiences at the Shed and their sense of belonging and social inclusion. Participants had any type of long-term disability and had been attending the shed for a minimum of 1 month. Data were collected between May and September 2013 and were analysed using the constant comparative method of grounded theory. The core theme that emerged was an enabling community space. The four sub-themes were: a community and social hub; an equalising space; a safe and supportive male environment; and meaningful male activities. The current literature exemplifies Men's Sheds to be important community-based organisations beneficial to men's health and well-being. For men living with long-term disabilities, this study illuminates that Men's Sheds offer an environment of equality, facilitating a collegial and egalitarian culture. Men can partake in enabling activities and enjoy the company of other men enhancing their sense of belonging and social inclusion as well as interact with other community groups that occupy the same space as the Men's Shed.